STUDENT AS "AN EDUCATION CONSUMER": CONTENT OF THE CONCEPT - Olga K. Krokinskaya; Sergey Yu. Trapitsin (Moscow Polytechnic University, 2016)
The purpose of this article is justification of students' status as consumers of educational products and users of education results. They are also characterized as competent agents to assess the quality of higher education. The subject of discussion is also a conceptual model of the main working concepts in the context of the problem. Sociological exchange theory is a methodological basis for the interpretation of the studied phenomena.The article deals with such concepts as education quality, students' assessment of education quality, educational product and its main consumers. The students' opinion is presented as a competent position to account for their views for designing educational politics of the University. The dynamics of the post!industrial shift of the main target groups of education consumers is shown in the article. This fact requires to change formulations of objectives of the University and to correct contents and modes of interaction between University and students. The arguments for individualization processes and learning outcomes for students are offered here. Thereby its importance to the strategic management of University is highlighted.